Tantangan Pendidikan Seni Rupa dan Desain Indonesia Sebuah Refleksi tentang Eksistensi 1 Dekade FSRD UK Maranatha - Kusbiantoro, Krismanto (Zenit, 2013)
The challenge of arts and design education in Indonesia refers to the issues of the significant quantity growth of schools and also students of arts and design regarding the problem of the loss of the “art and design” spirit, which is the poetic atmosphere of education. Nowadays, arts and design schools are obliged to meet all the formal administrative requirements as directed by the government. Lecturers are required to do both academic and administrative work like any other the non-arts and design schools; consequently, they are unconsciously trapped in administrative routines instead of their professional poetic acts.  Nigel Cross in “Designerly Ways of Knowing” suggests 3 cultural domains in terms of knowledge and human abilities, namely sciences, humanities and design which compromise themselves as the “head, heart and hand” aspects of education. Cross proposed design as a specific domain with regard  to its ability  to produce knowledge through the act of “creating”. Arts and design education therefore refers to a scientific education which is dominated by practical approaches as the “hand” aspect of education. In this sense, arts and design schools must be aware that the poetic atmosphere of education is very crucial not only for the lecturers but also for the students. Many efforts had been done in the first decade of the Faculty of Arts and Design at Maranatha  Christian University regarding this issue. Our arts and design education surely provides an excellent process of producing creative and  well-being persons. This paper is a reflection of what the Faculty of Arts and Design at Maranatha Christian University has done and will continuously do.   Keywords: arts and design education, poetic atmosphere of education, the “hand” aspect of education, creative and well-being persons